Building effective collaboration between health systems and the life sciences industry. Issue 7 (3rd October 2019) - da Fonseca, Elize Massard; Teixeira, Mariana Ramos; do Rosario Costa, Nilson
ABSTRACT: This viewpoint reflects on the challenges of promoting affordable and innovative medicines while fostering a competitive environment for research and development in developing countries. We explore the life sciences industrial policies of Brazil and the United Kingdom in order to identify mechanisms and conditions that could serve as lessons to practitioners in other countries. We suggest three crucial design attributes: a strategic collaboration between a health system and the private sector, coordination and accountability mechanisms, and a network of support (that is, embeddedness).